Retrospective assessment of fungal pathogens isolated from various clinical samples in a tertiary care hospital in Turkey: A cross-sectional study - Çolak, Meryem; Aşgın, Nergis (Journal of Surgery and Medicine, 2021)
Background/Aim: Fungal infections are an emerging health problem worldwide and can be caused by a broad variety of fungal pathogens. This study aimed to retrospectively determine and evaluate the fungal pathogens isolated from various clinical samples in our laboratory. Methods: A total of 996 clinical samples obtained from 803 patients who visited Karabuk University Training and Research Hospital microbiology laboratory between January 2019-December 2020 were included in this study. The BD-Phoenix 100 automated microbiology system was used for the identification of strains. Results: Among 803 patients, 52.4% were female and 47.5% were male. The median age of the patients was 76 (0-99) years. Urine (49%) and blood (27.6%) samples were evaluated the most. The most common fungal pathogen was Candida albicans (48.7%), followed by Candida tropicalis (16.5%), Candida parapsilosis (10.6%), Candida glabrata (9%), Saccharomyces cerevisiae (5.7%), and Trichosporon species (3.1%). While more than 90% of fungal strains were isolated from the inpatients, 9% were isolated from the outpatients (p<0.05). Among all, 69.4% of strains were isolated from the intensive care units, followed by internal medicine (5.5%), palliative care (5%), urology (3.6%), and orthopedics and traumatology clinics (2.1%). Conclusion: Although C. albicans is still the most common fungal pathogen, the incidences of non-albicans candida and other fungi are increasing worldwide. Therefore, each country should figure out its local fungal profile and update its antifungal treatment protocols accordingly.